Comparison of the Stress and Anxiety to Viral Epidemic-9 and SAVE-6 scales among healthcare workers in Peru - Gamonal, Bryan; Quispe-Lizano, Rogelio; Javier-Murillo, Nair; Lapeyre-Rivera, André; Perea-Flórez, Francisco; Velásquez-Rimachi, Víctor; Alva-Diaz, Carlos; Velazco-Gonzales, Gilberth; Ahmed, Oli; Chung, Seockhoon (Frontiers in Psychiatry, 2024)
Peru is a country that has a high incidence of viral outbreaks and epidemics, which is why it is necessary to validate a scale that measures anxiety and stress in professionals who are on the front lines of these events. Therefore, our objective was to validate the Peruvian-Spanish version of the Stress and Anxiety to Viral Epidemics-9 items (SAVE-9) scale and to concurrently compare its validity and internal consistency with the SAVE-6 scale among healthcare workers (HCWs). We conducted a cross-sectional study based on data collected from a self-reported survey in paper-and-pencil format between April and July 2023. A total of 203 HCWs participated in the research. We developed a confirmatory factor analysis (CFA) and item response theory (IRT). We calculated Cronbach's alpha coefficient and McDonald's omega to assess the internal consistency of the scales. The results show that for SAVE-9, a two-factor model and for SAVE-6, a one-factor model provided an excellent fit in the confirmatory factor analysis. Both scales demonstrated strong internal consistency (Cronbach's α 0.85 and 0.86, respectively). Significant correlations were found between the SAVE-9 and SAVE-6 scales and Generalized Anxiety Disorder-7 Items Scale (r=0.44 and r=0.38, respectively, p<0.001) as well as the Patient Health Questionnaire-9 Items (r=0.39 and r=0.35, respectively, p<0.001). Optimal cut-off points for SAVE-9 and SAVE-6 were identified for assessing anxiety, aligned with a GAD-7 score≥5 points. The Peruvian-Spanish SAVE-9 and SAVE-6 scales are reliable and valid rating scales to assess the anxiety response of HCWs in response to viral epidemics. Though COVID-19isdiminished,thesescaleswillbeusefulforotherviralepidemicsinthe future.